Essays on the economics of migration - Monscheuer, Ole (2018)
This dissertation consists of three essays that study the integration of immigrants in different contexts. The essays cover a broad variety of dimensions of integration, including outcomes of economic and social integration, and identify particular mechanisms that foster or impede assimilation.